2017
DOI: 10.1002/2017gl073524
|View full text |Cite
|
Sign up to set email alerts
|

Intensified dust storm activity and Valley fever infection in the southwestern United States

Abstract: Climate models have consistently projected a drying trend in the southwestern United States, aiding speculation of increasing dust storms in this region. Long‐term climatology is essential to documenting the dust trend and its response to climate variability. We have reconstructed long‐term dust climatology in the western United States, based on a comprehensive dust identification method and continuous aerosol observations from the Interagency Monitoring of Protected Visual Environments (IMPROVE) network. We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
170
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(192 citation statements)
references
References 68 publications
(108 reference statements)
2
170
1
Order By: Relevance
“…In combination with reduced water availability for irrigation, these factors may increase the number of dust storms, which are known to carry large numbers of fungal spores (Griffin, ). Dust storm activity in the United States increased in recent decades and has been linked to changes in valley fever incidence (Tong et al, ; Williams et al, ). Other short‐lived natural dust events, including a landslide triggered by an earthquake, have also been related to valley fever outbreaks (Harp & Jibson, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In combination with reduced water availability for irrigation, these factors may increase the number of dust storms, which are known to carry large numbers of fungal spores (Griffin, ). Dust storm activity in the United States increased in recent decades and has been linked to changes in valley fever incidence (Tong et al, ; Williams et al, ). Other short‐lived natural dust events, including a landslide triggered by an earthquake, have also been related to valley fever outbreaks (Harp & Jibson, ).…”
Section: Discussionmentioning
confidence: 99%
“…Soil disturbance from construction sites (California Department of Public Health, ; Wilken et al, ), military training (Smith, Beard, Rosenberger, et al, ), archaeological digs (Perera et al, ; Petersen et al, ; Werner & Pappagianis, ), and film shoots (Wilken et al, ) have been associated with valley fever outbreaks. Dust storms have also been correlated with increased incidence in a few, highly endemic Arizona counties (Tong et al, ) and have caused localized outbreaks of valley fever in California (Williams et al, ). Human soil disturbance may exacerbate these natural events, leading to increased exposure to Coccidioides spp.…”
Section: Introductionmentioning
confidence: 99%
“…Climate models consistently project that southwestern North America, a region containing extensive wind-erodible and human-disturbed drylands and deserts, will transition to an even more arid hydroclimate under continued greenhouse gas (GHG) forcing (Ault et al, 2016; Wehner et al, 2017). Recent studies suggest that such changes may lead to enhanced dust activity in the U.S. Southwest (Achakulwisut et al, 2017; Tong et al, 2017). In a previous study, Achakulwisut et al (2018) provided one of the first estimates of the climate-attributable impacts on fine dust (FD) and public health in the U.S. Southwest.…”
Section: Introductionmentioning
confidence: 99%
“…Using IMPROVE data, Hand et al (2016) found an increasing trend of fine dust in spring in the southwestern US during 1995-2014 and related this trend to a negative Pacific decadal oscillation (PDO) from 2007 to 2014. Tong et al (2017) also found a rapid increase in dust storm activity in the southwestern US from 1988 to 2011 and related the trend to sea surface temperature variations in the Pacific. Later, examined the trends of IMPROVE fine dust concentration in different seasons from 2000 to 2014 and found positive trends over the southwestern US in spring and over the central US in summer and fall.…”
Section: Introductionmentioning
confidence: 99%